Respuesta :
let x represent the first number=5
let y represent the second number =7
x+y=12 x+y=12 x+7=12
-1(x-y=2) + -x+y=-2 -7 -7
----------- -----------
0+2y=14 x=5
--------- Y=7
2 2
let y represent the second number =7
x+y=12 x+y=12 x+7=12
-1(x-y=2) + -x+y=-2 -7 -7
----------- -----------
0+2y=14 x=5
--------- Y=7
2 2
Answer:
The numbers are 7 and 5.
Step-by-step explanation:
Let two unknown numbers be x and y .
Assume [tex]x>y[/tex].
The first expression is given : The sum of two numbers is 12.
we have,
x+y =12 ...[1]
The second expression states that : The difference of two numbers is 2 , i.e,
we have;
x- y =2 .....[2]
Now, adding the equations, term by term on both sides, we will eliminate y leaving an equation in x that we can solve:
then, [1]+[2] gives
[tex]x+y+x-y = 12 +2[/tex]
Simplify we get;
[tex]2x = 14[/tex]
⇒ [tex]x= 7[/tex]
Substitute the value of x =7 in equation [1];
[tex]7+y =12[/tex]
On simplify, we get;
y = 5.